Exploring students' use of online sources in small groups with an augmented reality-based activity – group dynamics negatively affect identification of authentic online information. Issue 6 (June 2018) - Jahnke, Isa; Meinke Kroll, Michele
Abstract: In this study initially, we wanted to explore students' use of online sources and how they use online information to try to persuade each other when they get the group assignment to identify misleading from correct information. We grounded our concept on "OnLife" (Floridi, 2015) in which students used online information to find arguments for their actions. We created an AR-based campus tour for mobile devices in which students discussed content, identified correctness of online information and were asked to made a group decision. Four groups have been studied. Video-recorded observation and interviews were applied. During data analysis we found results that point to four distinctive patterns of relationships between social in-group dynamics and the identification of authentic online information: a) network of equal members, b) omission of one person, c) one person guides the others, d) no collaborative reasoning. The result is a 'Happy Surprise', it shows that social dynamics affected group performance stronger than equal access to online sources. Equal access to online information did not lead to a reasonable based-on-facts discussion. Group dynamics diminished the advantage of equal access and impacted decision-making more than the information itself. Because of the small study size, generalization of results is limited, but lays a foundation for follow-up or experimental studies.